2021
DOI: 10.3390/jmse9020206
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of an Oscillating Wave Surge Energy Converter

Abstract: So far, very few studies have focused on the quantification of the environmental impacts of a wave energy converter. The current study presents a preliminary Life Cycle Assessment (LCA) of the MegaRoller wave energy converter, aiming to contribute to decision making regarding the least carbon- and energy-intensive design choices. The LCA encompasses all life cycle stages from “cradle-to-grave” for the wave energy converter, including the panel, foundation, PTO and mooring system, considering its deployment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…A small number of LCA studies have been undertaken for Wave Energy Converters (WECs) [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Life Cycle Assessment Of Offshore Renewablesmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of LCA studies have been undertaken for Wave Energy Converters (WECs) [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Life Cycle Assessment Of Offshore Renewablesmentioning
confidence: 99%
“…The global warming potential (GWP) of WECs has been found to range from 23 gCO 2 e/kWh [7] to 105 gCO 2 e/kWh [11], as shown in Table 1. Many of these studies focus on lifecycle impacts only in terms of carbon and energy audits [7][8][9][10], but more recent publications have explored a wider range of metrics [11][12][13][14][15][16][17], accounting for additional ecosystem impacts such as eutrophication and ecotoxicity. The literature also highlights the impact of assumptions and scope of LCA studies, as some examples can be found where results differ for the same or similar input data.…”
Section: Life Cycle Assessment Of Offshore Renewablesmentioning
confidence: 99%
“…Wave power represents a considerable source of renewable energy, nevertheless, most of the Wave Energy Converters (WECs) developed still require further research and demonstration tests (Apolonia and Simas, 2021). As highlighted by Esteban et al (2017), the technology behind WECs is not mature enough to be developed industrially and the Levelized Cost of Energy (LCOE) remains too high.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the elastic synthetic rope has great potential in the application of wave energy converter (WEC) mooring system [2]. Moreover, the decommissioning process and reusement possibilities of synthetic ropes are being studied since this provides an opportunity for financial, environmental, and socioeconomic benefits [3,4].…”
Section: Introductionmentioning
confidence: 99%